Self-Powered Sensors Enabled by Wide-Bandgap Perovskite Indoor Photovoltaic Cells - Mathews, Ian; Kantareddy, Sai Nithin Reddy; Sun, Shijing; Layurova, Mariya; Thapa, Janak; Correa-Baena, Juan-Pablo; Bhattacharyya, Rahul; Buonassisi, Tonio; Sarma, Sanjay; Peters, Ian Marius (Advanced Functional Materials, 2019)
A new approach to ubiquitous sensing for indoor applications is presented, using low-cost indoor perovskite photovoltaic cells as external power sources for backscatter sensors. Wide-bandgap perovskite photovoltaic cells for indoor light energy harvesting are presented with the 1.63 and 1.84 eV devices that demonstrate efficiencies of 21% and 18.5%, respectively, under indoor compact fluorescent lighting, with a champion open-circuit voltage of 0.95 V in a 1.84 eV cell under a light intensity of 0.16 mW cm−2. Subsequently, a wireless temperature sensor self-powered by a perovskite indoor light-harvesting module is demonstrated. Three perovskite photovoltaic cells are connected in series to create a module that produces 14.5 µW output power under 0.16 mW cm−2 of compact fluorescent illumination with an efficiency of 13.2%. This module is used as an external power source for a battery-assisted radio-frequency identification temperature sensor and demonstrates a read range by of 5.1 m while maintaining very high frequency measurements every 1.24 s. The combined indoor perovskite photovoltaic modules and backscatter radio-frequency sensors are further discussed as a route to ubiquitous sensing in buildings given their potential to be manufactured in an integrated manner at very low cost, their lack of a need for battery replacement, and the high frequency data collection possible.
CRIS-Team Scopus Importer:2022-06-05
Keywords: energy harvesting; indoor photovoltaics; perovskite solar cell; RF backscatter; self-powered